2019
DOI: 10.1007/s10493-019-00349-5
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia raoultii and Rickettsia sibirica in ticks from the long-tailed ground squirrel near the China–Kazakhstan border

Abstract: Spotted fever group (SFG) rickettsiae cause infection in humans, domestic animals and wildlife. To date, no rickettsial agents have been reported in hard ticks from the longtailed ground squirrel (Spermophilus undulatus). A total of 50 adult ticks and 48 nymphs were collected from S. undulatus in the border region of northwestern China. Tick species (identified according to morphological and molecular characteristics) included Dermacentor nuttalli, Dermacentor silvarum and Ixodes kaiseri. Based on the cytochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…( 2019 ) 1 l China Zhao et al. ( 2019 ) 180 l China Zhang et al. ( 2019 ) 10 l Mongolia Hightower et al.…”
Section: Methodsmentioning
confidence: 99%
“…( 2019 ) 1 l China Zhao et al. ( 2019 ) 180 l China Zhang et al. ( 2019 ) 10 l Mongolia Hightower et al.…”
Section: Methodsmentioning
confidence: 99%
“…In China, eleven SFG Rickettsia species, Rickettsia sibirica, Rickettsia heilongjiangensis, Rickettsia aeschlimannii, Rickettsia conorii, Rickettsia felis, Rickettsia massiliae, Rickettsia monacensis, Rickettsia rickettsia, Candidatus Rickettsia jingxinensis, Rickettsia raoultii and Rickettsia slovaca, have been identified in tick vectors, Pathogens 2020, 9, 249 2 of 9 domestic animals and wildlife [5][6][7][8][9][10][11][12][13]. Several Rickettsia genotypes have been characterized as etiological factors of human rickettsiosis in the country, such as R. heilongjiangensis [14,15], R. sibirica subsp.…”
Section: Introductionmentioning
confidence: 99%
“…The ticks were morphologically identified according to the standard taxonomic keys as previously described [14]. From five ticks, the 16S rDNA gene was amplified following a previously reported protocol [15]. The corresponding 16S rDNA sequence was deposited in the GenBank database under the accession number MF106219.…”
Section: Sample Collection and Identificationmentioning
confidence: 99%
“…Four genetic markers, including 17 kDa antigen (17-kDa), citrate synthase (gltA), and outer membrane proteins A and B (ompA and ompB) genes were assessed within each sample to investigate the presence of rickettsiae [15]. The primers and PCR cycling conditions in this study are shown in Additional file 1: Text S1 and Table S1.…”
Section: Detection Of Rickettsiae Sequencing and Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation